Societal challenges and business leadership for social innovation. Issue 4 (13th August 2021) - Pless, Nicola M.; Murphy, Matthew; Maak, Thomas; Sengupta, Atri
Abstract : Purpose: Today's pressing global societal challenges are urgent and require substantial solutions and innovations that tackle the roots of a problem. These challenges call for new forms of leadership, stakeholder engagement and innovation. This paper aims to examine whether, why and how business leaders engage in social innovation. The authors argue that leadership perspective and motivation are important drivers for developing substantial social innovations suited to resolving societal challenges at their roots. More specifically, the authors propose that intra-personal factors (degree of care and compassion), an inter-relational perspective of leadership (shareholder versus stakeholder) and the corresponding leadership motivation (personalized versus socialized) may unveil what quality of social innovation (first-order versus second-order solutions) is pursued by a business leader. Implications for future research and practice are provided. Design/methodology/approach: The authors revisit the concept of social innovation and explore its connection with care and compassion. They suggest a series of propositions pertaining to the relationship between different configurations of leadership and different forms of social innovation. Findings: Responsible business leaders with an integrative leader trait configuration (stakeholder perspective, socialized motivation, high degree of care and compassion) are more likely to foster substantial second-order social innovations for uprooting societal problems than business leader with an instrumental leader trait configuration (shareholder perspective, personalized motivation, low degree of care and compassion). An organization's stakeholder culture plays a moderating role in the relation between leadership and social innovation. Social implications: This paper reveals a path for conceptualizing leadership in social innovation from a stakeholder perspective. Future research should investigate the role of business leaders, their mindsets, styles and relational competencies in co-creation processes of social innovation empirically. If the development of substantial second-order social innovations requires leaders with a stakeholder perspective and socialized approach, then this has implications for leader selection and development. Originality/value: This paper advocates for new kinds of leaders in facilitating and sustaining social innovations to tackle global societal challenges.